Mitophagy-associated biomarkers and macrophage involvement in pulmonary arterial hypertension: identification and functional implications - Zhang, Xiaoyu; Cheng, Liming; Xie, Jiahui; Ma, Xuejuan; Gui, Wenting; Chen, Jiaxiang; Liu, Kai; Ma, Runwei (Frontiers in Physiology, 2025)
BackgroundPulmonary arterial hypertension (PAH) is a progressive disorder characterized by pulmonary vascular remodeling and mitochondrial dysfunction. Recent studies have implicated impaired mitophagy in the pathogenesis of PAH; however, the underlying mechanisms and associated biomarkers remain insufficiently defined. This study used an integrative approach, incorporating bulk transcriptomic profiling, single-cell RNA sequencing (scRNA-seq), machine learning algorithms, and experimental validation to explore the relationship between mitophagy and PAH.MethodsDifferentially expressed genes were extracted from publicly available microarray datasets and intersected with mitophagy-related genes curated from the MitoCarta 3.0 database. Weighted gene co-expression network analysis, along with five distinct machine learning models, identified five candidate mitophagy-associated biomarkers: RRAS, BECN1, MFN1, HIF1A, and TAX1BP1. These genes demonstrated high diagnostic performance (area under the curve >0.9) across both training and validation cohorts. Immune cell deconvolution analysis indicated a marked increase in M1 macrophage infiltration in lung tissue from individuals with PAH. The scRNA-seq further localized the expression of these biomarkers predominantly to monocyte/macrophage populations and indicated distinct pseudotemporal expression trajectories during macrophage differentiation. Expression and co-localization of the identified biomarkers with autophagy and inflammation markers were subsequently validated using quantitative PCR, western blotting, and immunofluorescence in a monocrotaline-induced PAH rat model.Results and ConclusionThe findings underscore the involvement of mitophagy in the pathobiology of PAH and identify five macrophage-associated biomarkers with strong diagnostic potential. These results may inform future strategies aimed at early detection and targeted therapeutic interventions in PAH.